Real‐world treatment and prognostic factors for survival in ALK+ non‐small cell lung cancer (NSCLC) patients with brain metastases in China - Na Li; Mingying Xie; Zichao Zhou; Jiamin Sheng; Xiaoqing Yu; Yun Fan (Thoracic Cancer, 2023)
Abstract Background To explore the efficacy and prognostic factors of different treatment modalities on anaplastic lymphoma kinase (ALK)+ non‐small cell lung cancer (NSCLC) patients with brain metastases (BMs). Methods A total of 86 patients were enrolled into the study. They were divided into two cohorts based on their history of treatment with ALK tyrosine kinase inhibitors (ALK‐TKIs) prior to the incidence of BMs. ALK‐TKI‐naïve patients with BMs were included in cohort 1 (n = 59); patients who developed BMs after ALK‐TKIs treatment were enrolled in cohort 2 (n = 27). Prognostic factors related with overall survival (OS) when treated with ALK‐TKIs were assessed in multivariable analysis. Results With a median follow‐up of 41.8 months, the median OS was 34.8 months. In cohort 1, the OS, intracranial progression‐free survival (iPFS), and progression‐free survival (PFS) were 38.7 months (95% CI: 23.3 to 54.1), 18.5 months (95% CI: 9.6 to 27.4), and 19.1 months (95% CI: 13.7 to 24.5), respectively. Significantly improved OS and iPFS were noted in those patients in which second‐generation ALK‐TKIs versus crizotinib were initiated (OS: not reached vs. 29.0 months, p = 0.040; iPFS: 22.8 vs. 11.9 months, p = 0.035). In cohort 2, patients who experienced BMs as a result of the treatment failure of ALK‐TKIs had a median OS of 27.1 months. Considerable duration of stable disease in patients with measurable BMs was observed (iPFS: 11.5 months, 95% CI: 4.4 to 18.6; PFS: 12.2 months, 95% CI: 3.2 to 21.1). Conclusion Second‐generation ALK‐TKIs further improved the duration of intracranial response and survival in ALK+ NSCLC patients with BMs in a real‐world setting. The potent intracranial efficacy of second‐generation ALK‐TKIs might generate the lowered urgency of local treatment.